How to Design a Zero-Degradation Battery: Compensating for Loss of Lithium Inventory in LFP Cells with LFO Additives - Rawat, Sunil Kumar; Marinescu, Monica; Offer, Gregory James; O'Kane, Simon E. J.; Li, Ruihe (Meeting abstracts (Electrochemical Society), 2025)
Loss of lithium inventory (LLI) caused by side reactions in lithium-ion cells is one of the primary reasons behind their capacity fade and shorter cycle life. Research in academia and industry has explored additives such as Lithium Iron oxide (Li₅FeO₄) in LFP-based battery chemistries that sacrifice their lithium inventory to compensate for LLI. Over the last ~15 years [1-4], research has proven that LFO can compensate for LLI and help maintain stable cell performance, and more recently, CATL & Rimac [5-6] announced its commercial-level usage, claiming to have achieved zero degradation for extended periods. However, the specifics behind achieving such excellent performance are neither fully disclosed by them nor much explored in the literature. This work offers deeper insights into how exactly LFO can be employed in commercial LFP cells with LFP/LFO positive electrode (PE) and Graphite negative electrode (NE) using simulations run by building a full-cell physics-based model in PyBaMM. The work digs deeper into the science behind releasing lithium inventory from LFO and its impact on cell degradation (SEI, lithium plating), discharge capacity, and cell life. The work also attempts to find the optimal method to control lithium release from LFO and the optimum weight fraction of LFO to minimize cell degradation and achieve long-lasting, zero-degradation batteries. Work concludes that (a) the release of lithium inventory from additives can be controlled to maximize the benefits of their usage instead of releasing all their lithium inventory at once, (b) controlled slow lithium release maintains the cell balancing and reduces the degradation rates, while rapid lithium release can accelerate cell degradation (c) using optimum weight fraction of LFO is crucial for minimizing cell degradation as excess LFO even though appears beneficial because of its capability to provide more lithium inventory and higher usable cell capacity but is counterproductive as it promotes faster cell degradation resulting in shorter cycle life of the cell. Hence, this study advances and broadens the existing theoretical understanding of employing sacrificing agents, such as LFO, in commercial lithium-ion cells. Additionally, we conclude that merely adding lithium-rich additives does not promise high-performance batteries; instead, it depends on using them in optimal amounts and ensuring the controlled release of lithium inventory through appropriate control methods. References [1] Johnson, C. S., Kang, S.H., Vaughey, J. T., Pol, S. V., Balasubramanian, M., & Thackeray, M. M. Li₂O Removal from Li₅FeO₄: A Cathode Precursor for Lithium-Ion Batteries. Chemistry of Materials 22, 3 (2010). [2] Su, X., Lin, C., Wang, X., Maroni, V. A., Ren, Y., Johnson, C. S., & Lu, W. A new strategy to mitigate the initial capacity loss of lithium-ion batteries. Journal of Power Sources 324, 150-157 (2016). [3] Dose, W. M., Maroni, V. A., Piernas-Munoz, M. J., Trask, S. E., Bloom, I., & Johnson, C. S. Assessment of Li-Inventory in Cycled Si-Graphite Anodes Using LiFePO₄ as a Diagnostic Cathode. Journal of The Electrochemical Society 165, A2389-A2396 (2018). [4] Liu, X., Liu, J., Peng, J., Cao, S., Hu, H., Chen, J., Lei, Y., Tang, Y., & Wang, X. Addressing the initial lithium loss of lithium-ion batteries by introducing pre-lithiation reagent Li₅FeO₄/C in the cathode side. Electrochimica Acta 481, 143918 (2024). [5] Murray, C. Rimac using pre-lithiation for ‘zero capacity fade for first two years’ in BESS . Energy Storage News. (2024) . https://www.energy-storage.news/rimac-using-pre-lithiation-for-zero-capacity-fade-for-first-two-years-in-bess/ [6] Pathirana, T. CATL's SECRET to “Zero” Degradation Batteries: Unveiling the Potential of LFO Cathode Additives. LinkedIn Article (2024). https://www.linkedin.com/pulse/catls-secret-zero-degradation-batteries-unveiling-lfo-pathirana-yfsuc/ Figure 1